The Effects of Personal and Environmental Factors on the Process of Knowledge Sharing with the Role of Education Moderator - Mostafa Jafari; Peyman Akhavan; Sayyed Hojatollah Eshaqi (بازیابی دانش و نظام‌های معنایی, 2018)
Aim: The subject of knowledge sharing is one of the important challenges in knowledge management. According to the Bandura theory, personal factors, environmental factors, and behavior are in reciprocal relations with each other. In this research, the impact of environmental and individual factors on the attitude of knowledge sharing and also the effect of educational variables as a moderator between knowledge sharing attitude and knowledge sharing behavior have been investigated.Methodology: The method of this applied research is survey-correlation. The research population includes the staff of Allied Consulting Engineers Company, from which, 83 people were selected as sample based on simple sampling using Cochran's formula. The structural correlation validity, the research indicators with convergent and divergent validity models, and the reliability of the factor load indicators were valued at 0.8, while Cronbach's alpha coefficients and the reliability of the combinations were valued at 0.7.Findings: The findings show that independent structures (environmental and personal factors) with t values higher than 1.96 affect the dependent structure (knowledge sharing attitude); education moderating variable of GOF=0.408 has had a reverse effect on knowledge sharing attitude and knowledge sharing behavior.Conclusion:  The knowledge sharing approach influences the behavior of knowledge sharing, and the education variable, with respect to the signs of its factor load, inversely modulates behavior and suggests that the higher the education of the people, the less their willingness to share knowledge